Path planning for mobile articulated robots based on the improved A* algorithm. (24th August 2017) - Xu, Yaru; Liu, Rong
Mobile articulated robots system composed of tractor and multiple articulated trailers is a nonlinear and underactuated system subject to nonholonomic constraints. The significant achievements of path planning for mobile robots with single segment are very difficult to be applied to it directly. For resolving this problem, the kinematics model is established for the system with three segments connected by nonstandard connection type, as well as its trajectory. Equivalent size is introduced that includes two parameters: the distance parameter being the size for enlarging obstacles and the curvature parameter being the minimum turning radius of system. The distance parameter is used to enlarge obstacles in the environment to shrink the system to be a particle. The planning path adopted by the improved A* algorithm can ensure itself as a collision-free and feasible path as long as the maximum path curvature is no larger than the curvature parameter in free space. The comparisons of simulation result show that the improved A* algorithm makes the quality of path optimized and more suitable than A* algorithm under the complex environment.